2018
DOI: 10.1002/mnfr.201800147
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Roles of Flavonoids on Inflammasome Activation during Inflammatory Responses

Abstract: Inflammation is an innate immune response to noxious stimuli to protect the body from pathogens. Inflammatory responses consist of two main steps: priming and triggering. In priming, inflammatory cells increase expressions of inflammatory molecules, while in triggering, inflammasomes are activated, resulting in cell death and pro-inflammatory cytokine secretion. Inflammasomes are protein complexes comprising intracellular pattern recognition receptors (PRRs) (e.g., nucleotide-binding oligomerization domain-lik… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
72
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(74 citation statements)
references
References 140 publications
(328 reference statements)
1
72
0
1
Order By: Relevance
“…In addition, caspase-1 inhibitor, VX-765 completely diminished the course of inflammatory reaction and hypersensitivity (Stack et al, 2005). Yi (2018) reported that flavonoids in functional foods have an anti-inflammatory activity by reducing caspase-1 activities.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition, caspase-1 inhibitor, VX-765 completely diminished the course of inflammatory reaction and hypersensitivity (Stack et al, 2005). Yi (2018) reported that flavonoids in functional foods have an anti-inflammatory activity by reducing caspase-1 activities.…”
Section: Discussionmentioning
confidence: 97%
“…In addition, caspase‐1 inhibitor, VX‐765 completely diminished the course of inflammatory reaction and hypersensitivity (Stack et al, ). Yi () reported that flavonoids in functional foods have an anti‐inflammatory activity by reducing caspase‐1 activities. Caspase‐1 is also an upstream molecule of NF‐κB, which is transcription factor of inflammatory mediators in human mast cells and caspase‐1 inhibitor reduces the expression of TSLP (an initiation factor of AD) by the inhibition of NF‐κB (Moon & Kim, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanism proposed for inhibiting activation by flavonoids was based on the regulation of the expression of inflammasome components such as the amino-terminal pyrin domain (PYD), which interacts with the ASC pyrin domain (caspase recruitment domain) to initiate the assembly of the inflammasome; the central nucleotide binding and oligomerization domain (NACHT), which has the ATPase activity necessary for NLRP3 oligomerization after activation; and C-terminal leucine-rich repeat (LRR) domain, whose function has not yet been identified. These changes can prevent its assembly and lead to inhibition of caspase-1 activation and, consequently, maturation and secretion of pro-inflammatory cytokines [ 41 , 42 ].…”
Section: Sapindaceae Familymentioning
confidence: 99%
“…Thus, luteolin ( 6 ) is able to reduce the expression of interleukin-1 beta (IL-1β), a cytokine with a primary role in the inflammatory response, and interleukin-8 (IL-8), a chemokine that stimulates migration of immune cells. Another anti-inflammatory flavonoid found in T. esculenta seeds is rutin ( 10 ), which promotes the inhibition of the NLRP3 inflammasome activation through the negative regulation of the NLRP3, ASC and caspase-1 expression and reduced production of IL-1β and interleukin-18 (IL-18), which is also known as an interferon-γ inducing factor (IFN-γ) [ 41 , 48 ].…”
Section: Sapindaceae Familymentioning
confidence: 99%